The use of digital technology – Efficient modern equipment to implement philosophy patterns of liberal education - Nguyễn, Thái Hòa (Nxb Kinh tế, 2023)
The fourth industrial revolution (also known as the 4.0 revolution) with artificial intelligence, the digital age, and the rapid development of new technology has a substantial impact on all aspects of our socioeconomic lives, including university education. The effective use of digital technology in education will take advantage of its strengths and open our minds about humanities or social sciences in the spirit of liberal education, contributing significantly to educating people and enhancing leadership competencies in complex global contexts. The article overviews digital technology in the current trends of Vietnam's education and its influence on the philosophy paradigm of liberal education in recent social sciences and humanities branches in Vietnam.